Figure 1 in Selective predation on common voles by Tawny Owls and Long-eared Owls in winter and spring ... - Balčiauskas, Linas; Received, Laima Balčiauskienė; Online, Published (Zenodo, 2014)
Figure 1. Distribution of the body mass of Microtus arvalis individuals, trapped in October–April and preyed upon by both Strix aluco and Asio otus in winter and spring, as estimated from mandibles. ... : Published as part of Balčiauskas, Linas, Received, Laima Balčiauskienė & Online, Published, 2014, Selective predation on common voles by Tawny Owls and Long-eared Owls in winter and spring, pp. 242-249 in Turkish Journal of Zoology 38 (1) on page 245, DOI: 10.3906/zoo-1303-20, http://zenodo.org/record/13192107 ...